The concurrence of lung malignancies and organizing pneumonia - Vedachalam, Srikanth; Freihat, Mohammad; Alomari, Ahmed K.; Sears, Catherine R.; Al Nasrallah, Nawar (Frontiers in Oncology, 2026)
IntroductionOrganizing pneumonia (OP) is often considered a benign finding, but in some cases, it may be associated with underlying malignancy. With the increasing use of minimally invasive biopsy techniques, understanding the relationship between OP and lung cancer is critical to avoid delayed or missed diagnoses. This study aims to evaluate the prevalence of OP and lung malignancy and report characteristics of these cases.Material and methodsA retrospective review was conducted of all lung pathology reports at Indiana University from January 1, 2010, to January 1, 2023, encompassing over 8,000 cases. Cases with histopathologic diagnoses of OP with and without lung malignancy were identified; relevant clinical, radiologic, and follow-up data were extracted. Using language extraction, we identified pathology cases showing both organizing pneumonia and carcinoma (Cohort 1) and transbronchial biopsies identified as “organizing pneumonia” (Cohort 2). Cohort 2 was selected to reflect current clinical practice.ResultsIn Cohort 1 (n=57), 88% of samples demonstrating both organizing pneumonia and malignancy were obtained via surgical resection. Among these, squamous cell carcinoma accounted for 46% and adenocarcinoma for 37% of cases, with all T-stages represented (44% T1, 29% T2, 16% T3, and 11% T4). In this cohort, thirty-eight prior biopsy samples prior to surgery were reviewed; 76% revealed malignancy, but none showed definitive organizing pneumonia likely due to focal nature of OP. Cohort 2 (n=40), 7.5% of patients in whom organizing pneumonia was identified through minimally invasive bronchoscopic sampling were ultimately diagnosed with concurrent lung cancer. All required repeat tissue sampling for cancer diagnosis.ConclusionLung malignancy is known to be associated with OP. A high degree of suspicion should be maintained if OP is found on minimally invasive techniques, particularly if malignancy is strongly suspected.